2020
DOI: 10.1101/2020.06.12.20129858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic determinants of daytime napping and effects on cardiometabolic health

Abstract: Daytime napping is a common, heritable behavior, but its genetic basis and causal relationship with cardiometabolic health remains unclear. Here, we performed a genome-wide association study of self-reported daytime napping in the UK Biobank (n=452,633) and identified 123 loci of which 60 replicated in 23andMe research participants (n=541,333). Findings included missense variants in established drug targets (HCRTR1, HCRTR2), genes with roles in arousal (TRPC6, PNOC), and genes suggesting an obesity-hypersomnol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 98 publications
(163 reference statements)
1
19
0
Order By: Relevance
“…Genetic associations for sleep traits were obtained from published 9,10,12,21 and unpublished GWAS summary statistics in UK Biobank (UKB) participants of European ancestry (methodologic details given in Data S1; GWAS characteristics listed in Table S1). We considered GWAS for all sleep traits ascertained in UKB: sleep duration, 12 morning diurnal preference (also referred to as "chronotype"), 10 daytime napping frequency, 22 snoring, insomnia symptoms, 9 difficulty awakening, and daytime sleepiness 23 (phenotype definitions and GWAS procedures are provided in Data S1 and Table S2). We selected all available sleep traits so as to provide an unbiased survey of the relationship between sleep health and migraine.…”
Section: Sleep Traits In Uk Biobankmentioning
confidence: 99%
“…Genetic associations for sleep traits were obtained from published 9,10,12,21 and unpublished GWAS summary statistics in UK Biobank (UKB) participants of European ancestry (methodologic details given in Data S1; GWAS characteristics listed in Table S1). We considered GWAS for all sleep traits ascertained in UKB: sleep duration, 12 morning diurnal preference (also referred to as "chronotype"), 10 daytime napping frequency, 22 snoring, insomnia symptoms, 9 difficulty awakening, and daytime sleepiness 23 (phenotype definitions and GWAS procedures are provided in Data S1 and Table S2). We selected all available sleep traits so as to provide an unbiased survey of the relationship between sleep health and migraine.…”
Section: Sleep Traits In Uk Biobankmentioning
confidence: 99%
“…We would expect this to bias results towards the null. To address this, we identified subsets of genome-wide significance SNPs of some sleep traits (i.e., 108 for insomnia, 14 19 for daytime sleepiness, 18 17 napping, 19 and 72 for chronotype 20 ) in other independent GWAS that did not include UKB. Details of these subsets were provided in Supplementary Methods .…”
Section: Methodsmentioning
confidence: 99%
“…Our primary aim was to explore effects of sleep traits (i.e., insomnia, 14 sleep duration, 17 daytime sleepiness, 18 daytime napping, 19 and chronotype 20 ) on average glycaemic levels assessed by HbA1c in general population. Our secondary aim was to assess the effects of these sleep traits on non-fasting glucose levels.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that the interindividual variability in sleep traits is under substantial genetic control. Based on common genetic variations from genome-wide association studies (GWAS) in adults, a SNP-based heritability of 7.0% (Jansen et al, 2019) and 9.8% (Dashti et al, 2019) has been estimated for insomnia and sleep duration, respectively. These estimates are comparable with SNP-based heritability of other psychiatric traits [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent large genome-wide association studies (GWASs) in adults have identified 202 genetic loci associated with insomnia (Jansen et al, 2019) and 78 with self-reported habitual sleep duration (Dashti et al, 2019). Based on these studies, one can calculate quantitative polygenic risk scores (PRS), which represent individuals' genetic susceptibility for insomnia and sleep duration, as estimated by the additive effects of multiple alleles using summary statistics from GWAS.…”
Section: Introductionmentioning
confidence: 99%